Comparative efficacy of different acute reperfusion therapies for acute ischemic stroke: a comprehensive benefit-risk analysis of clinical trials - Tsivgoulis, Georgios; Alleman, John; Katsanos, Aristeidis H.; Barreto, Andrew D.; Köhrmann, Martin; Schellinger, Peter D.; Molina, Carlos A.; Alexandrov, Andrei V. (Brain and Behavior, 2014)
Numerous acute reperfusion therapies (RPT) are currently investigated as potential new therapeutic targets in acute ischemic stroke (AIS). We conducted a comprehensive benefit-risk analysis of available clinical studies assessing different acute RPT, and investigated the utility of each intervention in comparison to standard intravenous thrombolysis (IVT) and in relation to the onset-to-treatment time (OTT).A comprehensive literature search was conducted to identify all available published, peer-reviewed clinical studies that evaluated the efficacy of different RPT in AIS. Benefit-to-risk ratio (BRR), adjusted for baseline stroke severity, was estimated as the percentage of patients achieving favorable functional outcome (BRR1, mRS score: 0-1) or functional independence (BRR2, mRS score: 0-2) at 3 months divided by the percentage of patients who died during the same period.A total of 18 randomized (n = 13) and nonrandomized (n = 5) clinical studies fulfilled our inclusion criteria. IV therapy with tenecteplase (TNK) was found to have the highest BRRs (BRR1 = 5.76 and BRR2 = 6.82 for low-dose TNK; BRR1 = 5.80 and BRR2 = 6.87 for high-dose TNK), followed by sonothrombolysis (BRR1 = 2.75 and BRR2 = 3.38), while endovascular thrombectomy with MERCI retriever was found to have the lowest BRRs (BRR1 range, 0.31-0.65; BRR2 range, 0.52-1.18). A second degree negative polynomial correlation was detected between favorable functional outcome and OTT (R (2) value: 0.6419; P < 0.00001) indicating the time dependency of clinical efficacy of all reperfusion therapies.Intravenous thrombolysis (IVT) with TNK and sonothrombolysis have the higher BRR among investigational reperfusion therapies. The combination of sonothrombolysis with IV administration of TNK appears a potentially promising therapeutic option deserving further investigation.
EVALuna2:22321